2015
DOI: 10.1002/humu.22935
|View full text |Cite
|
Sign up to set email alerts
|

HMOX2Functions as a Modifier Gene for High-Altitude Adaptation in Tibetans

Abstract: Tibetans are well adapted to high-altitude environments. Among the adaptive traits in Tibetans, the relatively low hemoglobin level is considered a blunted erythropoietic response to hypoxic challenge. Previously, EPAS1 and EGLN1, the major upstream regulators in the hypoxic pathway, were reportedly involved in the hemoglobin regulation in Tibetans. In this study, we report a downstream gene (HMOX2) involved in heme catabolism, which harbors potentially adaptive variants in Tibetans. We first resequenced the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…In particular, a missense mutation in EGLN1 prevents hypoxia-induced and HIF-mediated enhancement of erythropoiesis [142]. Moreover, HMOX2 (heme oxygenase 2; downstream of HIF) has recently been identified as a relevant modifier of hb metabolism and contributor to high-altitude adaptation in Tibetan highlanders [143]. In addition, variants of the major upstream transcriptional regulator EPAS1 were also significantly associated with low hb concentrations in Tibetan highlanders [144].…”
Section: Long-term Changes Of the Cardiopulmonary System Due To Hymentioning
confidence: 99%
“…In particular, a missense mutation in EGLN1 prevents hypoxia-induced and HIF-mediated enhancement of erythropoiesis [142]. Moreover, HMOX2 (heme oxygenase 2; downstream of HIF) has recently been identified as a relevant modifier of hb metabolism and contributor to high-altitude adaptation in Tibetan highlanders [143]. In addition, variants of the major upstream transcriptional regulator EPAS1 were also significantly associated with low hb concentrations in Tibetan highlanders [144].…”
Section: Long-term Changes Of the Cardiopulmonary System Due To Hymentioning
confidence: 99%
“…HMOX2 recently has been proposed as a modifier of hemoglobin metabolism [39]. Other long-term resident populations of the Qinghai-Tibetan plateau (Sherpa and Ayurveda) as well as recent migrants to the area (Mongolians) show patterns of natural selection that are consistent with Tibetan adaptation [4043].…”
Section: Genetic Adaptations To High-altitude Hypoxiamentioning
confidence: 99%
“…Haase et al found that, under low-oxygen conditions, the body can stimulate the synthesis and release of erythropoietin through cellular oxygen-sensing pathways such as HIF-1X, thus promoting hemoglobin production and erythrocyte proliferation to adapt to a harsh environment (Haase, 2013). Yang et al (2016) found that HMOX2 (also known as HO-2, heme oxygenase 2) as a modified gene could regulate the metabolism of downstream hemoglobin in the hypoxic metabolic pathway, indicating a mechanism for genetic adaptation of the Tibetan population to low-altitude hypoxia. Zou et al (2008) identified 101 QTLs affecting RBCs traits on wild boar (Sus scrofa) chromosomes 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, and 13 .…”
Section: Introductionmentioning
confidence: 99%